Metabolic Dysfunction in the Regulation of the NLRP3 Inflammasome Activation: A Potential Target for Diabetic Nephropathy - Wenli Zhao; Le Zhou; Petr Novák; Xian Shi; Chuang Biao Lin; Xiao Zhu; Kai Yin (Journal of Diabetes Research)
Metabolic dysfunction plays a key role in the development of diabetic nephropathy (DN). However, the exact effects and mechanisms are still unclear. The pyrin domain-containing protein 3 (NLRP3) inflammasome, a member of the nod-like receptor family, is considered a crucial inflammatory regulator and plays important roles in the progress of DN. A growing body of evidence suggests that high glucose, high fat, or other metabolite disorders can abnormally activate the NLRP3 inflammasome. Thus, in this review, we discuss the potential function of abnormal metabolites such as saturated fatty acids (SFAs), cholesterol crystals, uric acid (UA), and homocysteine in the NLRP3 inflammasome activation and explain the potential function of metabolic dysfunction regulation of NLRP3 activation in the progress of DN via regulation of inflammatory response and renal interstitial fibrosis (RIF). In addition, the potential mechanisms of metabolism-related drugs, such as metformin and sodium glucose cotransporter (SGLT2) inhibitors, which have served as the suppressors of the NLRP3 inflammasomes, in DN, are also discussed. A better understanding of NLRP3 inflammasome activation in abnormal metabolic microenvironment may provide new insights for the prevention and treatment of DN.